Bryce Canyon National Park: Archeology of the Paunsaugunt Plateau - Eininger, Sue; Herhahn, Cynthia; Irwin, Donald; Wenker, Chris T. (the Digital Archaeological Record)
Bryce Canyon National Park encompasses 14,502 ha (35,835 acres) on the eastern edge of the Paunsaugunt Plateau, in Garfield and Kane counties in western south-central Utah. The park is internationally renowned for its unique erosional landscape, where brilliantly colored stone pillars and hoodoos descend from the eastern rim of the plateau and fill the precipitous canyons below the Pink Cliffs (Figure 1.1). The Bryce Canyon Archeological Inventory Survey (AIS) represents the first large-scale, comprehensive archeological survey conducted in the park. This volume summarizes the archeological data and presents the interpretations resulting from a comprehensive survey of most of the park land that lies on the top of the Paunsaugunt Plateau. The area surveyed covers 4,370 ha (10,799 acres). This effort began in 2000 with the creation of a research plan and sampling strategy. The fieldwork was conducted during the summers of 2000 and 2001, and the data processing, analysis, and research that resulted in this report were accomplished in 2002.